Dampak Penurunan Harga Karet Terhadap Kesejahteraan Keluarga Petani Di Desa Kertopati Tahun 2017-2021: Studi Kasus Di Kecamatan Mandiangin Kabupaten Sarolangun - Mustazila Mustazila; Eja Armaz Hardi; Ahmad Syahrizal (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to find out what impact the Kertopati village community felt as a result of a decrease in the price of rubber sap and how the Kertopati village community's efforts to improve welfare resulted from a decrease in rubber latex prices, this research is of a qualitative type. The object of this research is the entire community of Kertopati village who work as rubber farmers. The data sources used are primary data and secondary data. Data were obtained directly from 12 respondents using data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques. The results of the study show that: The impact they feel is the lack of fulfillment of their daily needs, they must try to find efforts to meet these needs, try to continue to complement clothing and food, and be able to meet social economic needs. The Kertopati village community must be able to survive, for the head of the household must be able to stand up to keep the family alive. The efforts they make, namely by carrying out new professions such as being construction workers, selling and even working with other people (ART), this proves that the efforts they are making are to continue to make ends meet and improve welfare.